Pengembangan Sistem Informasi Manajemen Pengelolaan Dana Donatur Berbasis Web (Studi Kasus : Yayasan Angel Hearts Bali) - Putu Sumada; I Nyoman Yudi Anggara; Ni Made Estiyanti (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2020)
The development of information technologies that support each other has given rise to the concept of Internet-based information technology, which is now becoming more widespread and more widely used in the conduct of a company's business in various fields. A management information system is designed to meet the general information needs of managers within a company. A non-profit company/organization, such as a foundation. The Angel Hearts Bali Foundation is a social organization that manages and connects donors who wish to donate or donate their assets for distribution to those in need, such as the needs of orphans, low-income communities, sick people, surgical houses, victims of natural disasters. and educational assistance. Several systems are in operation, namely donor registration services, cash donor transactions, donor data reporting and transactions with received donor funds (donations). The author is developing a management information system for managing donor funds, which includes donor registration, donation transactions, donation management, distribution of donor funds and a donation report for both donors, as well as an Angel Hearts Bali Foundation reporting report with the title Network Information Development donor fund management systems at Angel Hearts Bali Foundation, where research uses the Waterfall research method to conduct structured research with predetermined milestones that must be completed first in order to move on to the next phase. This system builder uses DFD, ERD and PhpMyadmin as the programming language to build the network.